2019
DOI: 10.1016/j.ekir.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Removal During High-Volume Peritoneal Dialysis in Acute Kidney Injury Patients: A Prospective Cohort Clinical Study

Abstract: IntroductionVancomycin pharmacokinetic data in patients with acute kidney injury (AKI) on high-volume peritoneal dialysis (HVPD) are lacking. The aims were to study the pharmacokinetics of i.v. vancomycin in patients with AKI treated by HVPD who received an i.v. dose of vancomycin (15–20 mg/kg), to determine the vancomycin removal, and to establish vancomycin dosing and evaluation pharmacokinetics target attainment achievement for the empirical treatment of patients with AKI treated by HVPD.MethodsVancomycin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Some researchers have suggested that teicoplanin could be used as an alternative to vancomycin to treat infections caused by MRSA or other resistant gram-positive organisms (Wood, 1996;Wood, 2000;Svetitsky, Leibovici, Paul, 2009;Yoon et al, 2014). Both teicoplanin and vancomycin are mainly excreted through the kidney and hence their elimination half-life is prolonged in patients with renal failure (Li et al, 2017;Ponce et al, 2018). Considering that the maintenance dose of teicoplanin is onceper day and that it has a lower rate of dose-related nephrotoxicity, teicoplanin is likely to be superior to vancomycin for clinical antibacterial application (Svetitsky, Leibovici, Paul, 2009;Shime et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have suggested that teicoplanin could be used as an alternative to vancomycin to treat infections caused by MRSA or other resistant gram-positive organisms (Wood, 1996;Wood, 2000;Svetitsky, Leibovici, Paul, 2009;Yoon et al, 2014). Both teicoplanin and vancomycin are mainly excreted through the kidney and hence their elimination half-life is prolonged in patients with renal failure (Li et al, 2017;Ponce et al, 2018). Considering that the maintenance dose of teicoplanin is onceper day and that it has a lower rate of dose-related nephrotoxicity, teicoplanin is likely to be superior to vancomycin for clinical antibacterial application (Svetitsky, Leibovici, Paul, 2009;Shime et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Our results were higher than those found by Golestaneh et al [36], which presented a reduction of 36% in 10 patients receiving PHD with a duration of at least 8 h. When they analysed the removal of vancomycin from dialysate in patients with sepsis and AKI treated with PHD using high-flux membranes, Kielstein et al [37] observed 26% removal of vancomycin from the dialysate. In a study by our group, the removal of vancomycin through high-volume peritoneal dialysis was 21.7% [38].…”
Section: Discussionmentioning
confidence: 98%
“…We should remember that in most settings, renal replacement therapy in the Intensive Care Units is still associated with at least 50% in mortality rate [10,[16][17][18] obviously, the current status quo of practice (and knowledge) is insufficient and the one thing that cannot be justified is inertia. To mention just a few examples, there is exciting literature emerging on fluid overload and volume determination in critically ill patients with acute kidney injury (AKI) [19][20][21][22], the impact of other organ failures (liver, heart) in AKI [23], on peritoneal dialysis as a viable alternative for continuous renal replacement therapy [24,25] and on the uniqueness of medication dosing in those with critical illness receiving renal replacement therapy [26,27]. All these issues will likely expand in the future and attract a global readership.…”
Section: Greetings To the Readersmentioning
confidence: 99%